A detailed study on improving the properties and performance aspects of biodiesel. Issue 1 (31st December 2022) - Rajan, K.; Rajaram Narayanan, M.; Suresh Kumar, S.; Parthasarathi, R.; Mohanavel, Vinayagam
ABSTRACT: This study scrutinises the effect on the appliance of microwave heating (MH) on the transesterification of palm oil and analyses its outcome on engine performance. Biodiesel is formed by two methods: one is straight and the other is MH that assists in transesterification. Both methods require a similar amount of palm oil, Methanol and KOH. Biodiesel primed by the straight practice is referred to as PBD. In the new method, the heating procedure is substituted by MH and hence the acquired biodiesel is referred to as PBDMW. The result found that PBD involves about 63 min for 74% yield, while the modified fuel (PBDMW) requires just 3.2 min for the 89% conversion. Performance experiments were performed on a diesel engine using PBD and PBDMW at the same situation. Experimental outcome demonstrates that the PBDMW has lesser BSFC (0.5 kg/kWh), EGT (22°C) and higher BTE (0.6%) than PBD due to its superior properties.